Phytophysiognomy of vegetation cover on the island of Colares in the Northeast of Pará (Research, Society and Development, 2021)
The effects resulting from the disorderly occupation and forest fires for the implantation of pasture and the increase of urban centers are the major problems in the 21st century, which have triggered major changes in the forest composition in the municipalities of Pará. As a result of the current situation, geoprocessing becomes an aid tool in the monitoring and management of environmental change processes. Associated with the Normalized Difference Vegetation Index (NDVI) technique, which enables the study of the dynamics of vegetation cover and the mechanisms correlated to land use and occupation. Thus, the objective is to analyze the vegetation cover with emphasis on the characterization of the fragments of arboreal vegetation present in the landscapes of Ilha de Colares. Using Landsat 8 ETM+ satellite image, OLI scene sensor - 223/061 and 223/061 in the period of 07/16/2017 and 06/15/2018, spectral sensor OLI (Operation Land Imager) and thermal TIRS (ThermalInfrared Sensor) made available by Science for Changing world – USGS. The generated product was divided into 6 reflectance intervals in each of the years analyzed. The results point to increased anthropogenic action in the region under study and the appearance of undergrowth in the interior areas of the island's coastal plain and fragmentation of dense forests along the region.